Implementasi Smart City Dalam Mendukung Pembangunan Berkelanjutan (SDGs) di Kota Cilegon - Wahyuningsih, Putri; Kurniawan, Irvan Arif; Prasetyo, Eko (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Cilegon City Government has launched around 117 programs to create smart cities in Cilegon City. The success rate of implementing smart city in Cilegon City itself until 2022 is 72%. Of the 117 planned programs, 84 have been implemented. Smart city implementation in Cilegon City began in 2019. Mayor Regulation Number 68 of 2016 which supports the implementation of smart cities, and the lack of human resources who master technology are inhibiting factors for smart city implementation in supporting sustainable development. development in Cilegon City. However, regulations that support smart city implementation are factors that support smart city implementation. In this review, the creators use a decidedly subjective methodology. according to the findings of this study 15 out of 17 sustainable development goals have been implemented in Cilegon City, the application of smart cities in Cilegon City is in line with sustainable development goals.